2018
DOI: 10.1177/0263617418781903
|View full text |Cite
|
Sign up to set email alerts
|

Desorption characterization of methane and carbon dioxide in coal and its influence on outburst prediction

Abstract: Coal and gas outburst is a dynamic phenomenon with violent eruptions of coal and gas from the working coal seam. It has been proved that the rapid desorption within a short period is necessary for the occurrence of an outburst. Due to limitation of the present test condition, gas desorption characterization for the first 60 s has not been researched sufficiently. In the present study, an experimental apparatus with the ability of high-frequency data collection was developed. Initial desorption characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The experiment was carried out strictly according to the technical standard of AQ 1080-2009 (Liang et al, 2018). In order to accurately describe the process of the experiment, this paper makes a schematic diagram of the determination system, as shown in Figure 4.…”
Section: Experimental Process and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was carried out strictly according to the technical standard of AQ 1080-2009 (Liang et al, 2018). In order to accurately describe the process of the experiment, this paper makes a schematic diagram of the determination system, as shown in Figure 4.…”
Section: Experimental Process and Resultsmentioning
confidence: 99%
“…The initial velocity of gas diffusion of coal is an index that indicates how quickly the coal containing gas changes from adsorption state to free state under the condition of complete exposure. The greater the initial velocity of gas diffusion, the stronger the initial gas release capacity of coal body, and the greater the outburst risk of coal seam (Liu and Wang, 2013;Liang et al, 2018;Sun, 2018). This index has been used as one of the indexes to judge the danger degree of coal and gas outburst in most countries in the world, and has been widely used (AQ1080-2009(AQ1080- , 2009Wang and Shi, 1991;Lu, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the gas desorption performance of coal was more profound. Studies have shown that as the gas adsorption pressure is increased, the initial velocity of coal gas desorption is signi cantly increased [32]. e corresponding cumulative gas desorption amount is greater for the same amount of time, and a higher gas pressure promotes the gas desorption of coal.…”
Section: E Ect Of the Pressure On The Desorption Characteristics Ofmentioning
confidence: 99%
“…The single-index method can easily predict coal and gas outbursts; however, its prediction accuracy is poor, and the critical value of the prediction index is difficult to determine. In each mine investigated, the most commonly used prediction methods are the number of drilling cuttings [16], initial gas emissions [17], initial gas desorption characteristics [15], debris index [18], and gas desorption index [19]. The outburst risk can be determined by collecting and comparing the corresponding indices during drilling operations.…”
Section: Introductionmentioning
confidence: 99%